2020
DOI: 10.1186/s40410-020-00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil releasing as key to rethink water spaces in urban planning

Abstract: Soil sealing processes that involved European cities in the twentieth century have reduced the quantity and quality of permeable soils (open land for agricultural and leisure resources). These processes have also weakened the ability of urban areas to manage natural events, of all evidence regarding the water cycle. This intense phase was supported by a cycle of growth that showed signs of an irreversible crisis only in the last decade, starting a new and unprecedented season. However, soil sealing development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…De-sealing the ground surface can improve water quality downstream by allowing runoff to be absorbed and toxins to be metabolized within the soil. Adobati and Garda enumerate the benefits of de-sealing in their study of the urban and semi-urban environment of Italy's Lombardy Region [78]. Maienza et al demonstrated that soils quickly return to life after de-sealing, even without adding exogenous topsoil [79].…”
Section: Discussionmentioning
confidence: 99%
“…De-sealing the ground surface can improve water quality downstream by allowing runoff to be absorbed and toxins to be metabolized within the soil. Adobati and Garda enumerate the benefits of de-sealing in their study of the urban and semi-urban environment of Italy's Lombardy Region [78]. Maienza et al demonstrated that soils quickly return to life after de-sealing, even without adding exogenous topsoil [79].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various initiatives to disincentive excessive land use consumption have been widely experimented in Europe. Among others, it is worth mentioning the cases of the Development and Maintenance Fee applied in the region of Upper Austria (Austria), the double urbanization fee in Emilia Romagna (Italy) and the soil compensation account introduced in Dresden (Germany) [55]. In the Austrian case the initiative establishes that the infrastructure fee is the responsibility of the owner, in order to limit urban expansion, while the Emilia Romagna region decided (by resolution No.…”
Section: Rules and Legal Devicesmentioning
confidence: 99%
“…It implies increasing health costs due to crashes whose risk for road users is higher than citizens' exposure to natural or anthropogenic events [4], even at the district scale [5]. On the other hand, social consequences in terms of the liveability of urban spaces [6], noise [7,8], air pollution [9,10], urban heat island [11], soil contamination and imperviousness [12,13], congestion [14,15], and neighbourhood unsatisfaction [16] cannot be overlooked. Due to increasing environmental attention, a new consciousness is changing how citizens move across the city [17], and slow and light mobility plays a pivotal role in this cultural change promoted after the COVID-19 outbreak [18].…”
Section: Introductionmentioning
confidence: 99%